The Spindle-Associated Microcephaly Protein, WDR62, Is Required for Neurogenesis and Development of the Hippocampus - Shohayeb, Belal; Ho, Uda Y.; Hassan, Halah; Piper, Michael; Ng, Dominic C. H. (Frontiers in Cell and Developmental Biology, 2020)
Primary microcephaly genes (MCPH) are required for the embryonic expansion of the mammalian cerebral cortex. However, MCPH mutations may spare growth in other regions of the developing forebrain which reinforces context-dependent functions for distinct MCPH genes in neurodevelopment. Mutations in the MCPH2 gene, WD40-repeat protein 62 (WDR62), are causative of primary microcephaly and cortical malformations in humans. WDR62 is a spindle microtubule-associated phosphoprotein that is required for timely and oriented cell divisions. Recent studies in rodent models confirm that WDR62 loss or mutation causes thinning of the neocortex and disrupted proliferation of apical progenitors reinforcing critical requirements in the maintenance of radial glia. However, potential contributions for WDR62 in hippocampal development had not been previously defined. Using CRISPR/Cas9 gene editing, we generated mouse models with patient-derived non-synonymous missense mutations (WDR62V66M and WDR62R439H) and a null mutation (herein referred to as WDR62Stop) for comparison. We find that WDR62 deletion or mutation resulted in a significant reduction in the thickness of the hippocampal ventricular zone and the area of the dentate gyrus (DG). This was associated with the mitotic arrest and depletion of radial glia and intermediate progenitors in the ammonic neuroepithelium. As a consequence, we find that the number of mitotic dentate precursors in the migratory stream and granule neurons in the DG was reduced with WDR62 mutation. These findings reveal that WDR62 is required for neurogenesis and the growth of the hippocampus during embryonic development.